Controlling Congestion by using Cluster Routing as a Gateway in WSN - Jain, Anamol Chand; Saxena, Ashendra Kumar (International Journal of Computer Sciences and Engineering, 2018)
For extending the lifespan of a wireless sensor network we apply a well-known technique known as cluster. In this technique we select cluster chiefs (CC) which are responsible for routing and regulate liabilities and this technique continuously interchanges the role of dispersed energy ingestion between nodules. As the main objective is saving energy so that throughput, packet delivery ratio strengthens and end-to-end delay may decrease. For this purposes sensory nodules are organised in such a way so that it may sense, calculate, and interconnect warnings in a WSN for prevention of gateway overcrowding. Cluster founded procedure is favoured because usual transportation methods consumes extra energy in sensing and calculating. For the purpose of preserving energy and to escape overcrowding throughout in multiclass traffic flow a novel approach for governing overcrowding on gateway is used. In which nodules are structured dynamically into clusters to offer whole exposure and connectivity. It calculates overcrowding. There is a suitable queue model in each mobile nodule inside the cluster for scheduling prioritized packet for the period of overcrowding without drop or delay. Simulation results shows that throughput, packet delivery ratio strengthens and end-to-end delay are decreases in comparison with other existing phenomenon.